Theoretical rationalisation for the mechanism of N-heterocyclic carbene-halide reductive elimination at CuIII, AgIII and AuIII. Issue 28 (18th March 2016) - Younesi, Yasamin; Nasiri, Bahare; BabaAhmadi, Rasool; Willans, Charlotte E.; Fairlamb, Ian J. S.; Ariafard, Alireza
Abstract : A dichotomy in carbon versus bromide reductive elimination in Cu III –NHC complexes is rationalized by computational methods (DFT). Abstract : Reductive elimination of imidazolium salts from Cu III is extremely sensitive to the anionic ligand (X or Y) type on Cu ( e.g. ΔG ‡ ranges from 4.7 kcal mol −1 to 31.8 kcal mol −1, from chloride to benzyl). Weakly σ-donating ligands dramatically accelerate reductive elimination. Comparison with Ag/Au shows that the HOMO energy, strength of M–NHC and M–Y bonds and inherent stability of M III with respect to M I are critical to governing reaction feasibility.